SAT0434 Network meta-analysis on the efficacy of novel therapeutic agents in patients with psoriatic arthritis. (15th June 2017) - Cheung, TT; Tsoi, MF; Fei, Y; Lau, CS; Cheung, BMY
Abstract : Background: Novel therapeutic agents are more effective than DMARDs in the management of psoriatic arthritis. However, direct comparisons of efficacy between these novel therapeutic agents are lacking. Objectives: This network meta-analysis aims to compare the relative efficacies between different novel therapeutic agents. Methods: Literature searching was conducted in MEDLINE, EMBASE, Scopus, ISI Web of Science, Cochrane Library, Clinicaltrials.gov and recent rheumatology conference abstracts up to Nov 2016. 2 independent researchers analysed the articles. For inclusion, randomised, placebo-controlled trials must report the proportion of patients achieving ACR20, ACR50, ACR70 and PASI75 responses. The outcomes of this network meta-analysis were the proportion of patients achieving ACR20, ACR50, ACR70 and PASI75 responses with reference to placebo and etanercept. Results were analysed using random effect model by R statistics (version 3.3.1) with statistical package netmeta (version 0.9–2). The heterogeneity of the study results was determined by the I 2 statistics. Results: 18 trials were included into this study. In general, all novel therapeutic agents demonstrated superior efficacies than placebo. With reference to etanercept, apremilast and ustekinumab were associated with less proportions of patients achieving ACR20 response (odds ratio [95% confidence interval]: 20mg apremilast: 0.18 [0.07–0.48]; 30mg apremilast: 0.24 [0.09–0.62]; 45mg ustekinumab: 0.26 [0.09–0.73]; 90mg ustekinumab: 0.32 [0.11–0.90]). Etanercept was not different from apremilast, ustekinumab, golimumab, adalimumab, ixekizumab, certolizumab, ixekizumab and secukinumab in terms of ACR20 and ACR50 responses. Golimumab and infliximab were associated with greater proportions of patients achieving PASI75 response, though the difference did not reach statistical significance. (odds ratio [95% confidence interval]: golimumab: 3.51 [0.44–28.2]; infliximab: 5.97 [0.89–40.2]). Conclusions: Apremilast and ustekinumab were less efficacious than etanercept in terms of ACR20 response. All the novel therapeutic agents demonstrated comparable efficacies in terms of ACR50, ACR70 and PASI75 responses. Disclosure of Interest: None declared